Draft Annual Plan 2005-06 Volume-I Government of Orissa - Planning Commission (Planning Commission, 2005)
Orissa is endowed with vast natural resources and has a tremendous potential for economic development. The State has also made considerable progress during the past 50 years. However, it continues to be one of the less developed states with 47.15 percent of its total population living below poverty line as per estimates of 1999-00. This calls for appropriate policy initiatives to transform State’s relatively underdeveloped economy, characterised by high incidence of poverty and un-employment, low per capita income, inadequate exploitation of abundant natural resources and inadequate development of socio-economic infrastructure, into a vibrant economy on the path of self sustaining economic growth with equity.
Government of Orissa, Planning and Coordination Department